Low-volume resistance training: a feasible, cost-effective strategy for musculoskeletal frailty in older adults attending daycare centers - Abreu, Frederico; Rodrigues, André; Baptista, Fátima (Frontiers in Sports and Active Living, 2025)
IntroductionFrailty is a prevalent geriatric syndrome, posing significant health risks for older adults attending daycare centers or residing in institutional settings. Addressing frailty with interventions that are feasible and cost effective and also promote high adherence within these environments is crucial.ObjectiveThis study aimed to evaluate the impact of a low-volume, remotely supervised resistance training protocol on physical frailty among frail older adults attending daycare centers. Secondary outcomes included changes in sarcopenia prevalence and fall risk.MethodsThirty-one frail older adults participated in a 12-week usual care period, followed by a 12-weeks intervention featuring low-volume (10-minute sessions) resistance training three times weekly. The program was delivered locally by non-specialized staff under remote supervision. Musculoskeletal, functional, and clinical assessments were conducted at three-time points: baseline, pre-intervention, and post-intervention.ResultsDuring the usual care period, a decline was observed in handgrip strength (19.2–18.5 kg) and sit-to-stand time (14.5–17.4s) (p < 0.05). However, these measures were preserved during the intervention. Relative muscle power decreased during the usual care but improved with training (4.3–5.2 W/Kg, p < 0.001). While body composition, physical function, gait speed, and Short Performance Physical Battery scores remained stable, reductions were observed in exhaustion and physical inactivity prevalence (p < 0.05). Frailty prevalence showed a decreasing trend (48%–26%, p = 0.099), with significant reductions in sarcopenia prevalence (29%–10%, p = 0.045), and fall frequency (p = 0.022).ConclusionThe low-volume strength training protocol was a feasible, cost-effective strategy for mitigating musculoskeletal frailty criteria, sarcopenia and fall risk among older adults in daycare centers, potentially delaying the progression of these conditions.